Evaluasi Sistem Informasi Akuntasi Penjualan Dalam Meningkatkan Pengendalian Internal Pada PT. Centra Nusa Indonesia - Selma Nevira Shinta Putri; Anindya Frysa Irsyadi; Irda Agustin Kustiwi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to evaluate the Sales Accounting Information System at PT. Celntra Nusa Indah. PT. Celntra Nusa Indonesia is a company operating in the field of coal trading (Coal Trading). From the evaluation results of the Sales Accounting Information System, it was obtained. Sales Accounting Information System at PT. Celntra Nusa Indonesia is good but still has several weaknesses. This can be seen from the clear organizational structure, but there are still weaknesses, namely that there is a combination of functions and responsibilities as follows: The cashier section which also doubles as the accounting section. The combination of these two functions can provide opportunities for employees to commit fraud by changing the accounting records to cover up the fraud. done. Division of duties and responsibilities at PT. Celntra Nusa Indonesia still has shortcomings. This can be based on research results which show that there is a division and implementation of duties and responsibilities that are not appropriate as follows: The billing department should be in charge of making extraordinary billing reports and collecting bills from customers. This is because the billing department receives proof of receipt of the invoice from the customer, where information is provided regarding the date it was received, the amount of payment and the time the invoice was paid. If this is done by the invoice department, it is still not completed. Because the invoice department has made daily billing reports.